Treasurer Professional Competence in Ma'ariful Ulum Islamic Boarding School, Banyuasin Regency Financial Administration - Siti Zubaidah; Atrika Iriani; Doris Febriyanti; Andika (Jurnal Studi Sosial dan Politik, 2024)
This study aims to analyze the professional competence of treasurers in financial administration at the Ma'ariful Ulum Islamic Boarding School in Banyuasin Regency and identify obstacles faced in the financial management process. This study uses a qualitative method with a descriptive approach. Data collection techniques were carried out through observation, interviews, and documentation, with research subjects including the treasurer of the Islamic boarding school, the head of the boarding school, and staff related to financial management. The results of the study indicate that treasurers have carried out financial recording, management, reporting, and accountability routinely. Treasurers also demonstrate an attitude of responsibility, integrity, and discipline in managing financial transactions. However, the professional competence of treasurers still needs to be improved, especially in aspects of understanding accounting standards for non-profit entities, the application of Interpretations of Financial Accounting Standards (ISAK) 35, the use of financial administration technology, and the preparation of systematic financial reports. The main obstacles found include limited accounting training, a manual recording system, the absence of written standard operating procedures, and limited access to financial information. Therefore, Islamic boarding schools need to improve the competence of treasurers through training, formulating financial management policies, and starting to implement technology-based administration systems so that financial governance becomes more effective, efficient, transparent, and accountable.